On brachypterous phaneropterine katydids (Orthoptera: Tettigoniidae:Phaneropterinae) from the Iguaçu National Park, Brazil: three new species, new record and bioacoustics - Fianco, Marcos; Preis, Hemanueli; Szinwelski, Neucir; Braun, Holger; Faria, Luiz R. R. (Zootaxa, 2019)
The species of brachypterous Phaneropterinae (Tettigoniidae) inhabiting the Iguaçu National Park, Paraná, Brazil, were studied. Four species have been recognized, Anisophya melanochloris (Rehn, 1911) and three new species described here: Anisophya una sp. n., as well as Xenicola taroba sp. n. and Xenicola xukrixi sp. n. We present relevant characters used in Orthoptera taxonomy, such as male genitalia, male and female stridulatory files, cerci and subgenital plates for all four species. Calling songs of three species are also described. X. xukrixi sp. n. stands out by its high carrier frequency with a peak above 70 kHz.